Trigonometric Finger Learning Media to Improve Mathematics Learning Outcomes of High School Students - Bilqis, Sayyidah; Aswad A, Muhammad Hajarul; T, Irma (Yayasan Insan Literasi Cendekia (INLIC) Indonesia, 2024)
Learning media in mathematics education is one of the determining factors for students' learning outcomes in mathematics. This study developed the Trigonometric Finger Learning Media (Jargonometry) to improve the mathematics learning outcomes of high school students. The research design an R&D approach using the ADDIE model. The study was conducted at a high school in East Luwu Regency, with Class X.8 from the 2023/2024 academic year as the research subjects. Data were collected through observation, interviews, product validation, response questionnaires, and learning outcome tests. The findings indicate that the Jargonometry learning media is valid, practical, and effective in improving high school students' mathematics learning outcomes.